Battery
By adding specific additives to the electrolyte of the lithium-ion battery, the electrolyte is promoted to electrically polymerize and adhere to the negative electrode surface during the battery operation, solving the problem of electrode interface damage during the cycle of silicon-based lithium-ion batteries, and improving the battery interface flatness and fast charging and circulation performance.
Patent Information
- Application Number
- CN202510094491.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-21
- Publication Date
- 2025-04-29
AI Technical Summary
Silicon-based lithium-ion batteries are prone to electrode interface damage during circulation, resulting in reduced Coulombic efficiency and cycle life and poor fast charging and circulation capabilities.
A battery is adopted, including an electrolyte solution and a negative electrode sheet. A first additive and a second additive are added to the electrolyte solution. The first additive forms a long-chain hydrocarbon-based polymer and by-products Li2SO4 and Li2CO3 by deestering the ester group. The second additive structure contains unsaturated alkynes at both ends, polymerizes to form a long-chain polymer, adheres to the surface of the positive and negative electrodes, and maintains a flat interface.
By maintaining the flat interface of the battery, the volume expansion and crushing of the silicon negative electrode are improved, and the fast charging cycle stability and cycle life of the battery are improved.
Smart Images

Figure CN119905637A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of batteries, and in particular to a battery. Background Art
[0002] Silicon has a very high theoretical specific capacity (4200mAh / g), low lithium insertion potential, and can provide Li in multiple directions. + The silicon-based lithium-ion battery has a de-embedding channel, but there are problems such as poor conductivity, easy crushing of particles, unstable growth of SEI, and volume expansion. These problems ultimately lead to reduced Coulomb efficiency and cycle life of silicon-based lithium-ion batteries, and poor fast charging and cycling capabilities of batteries. Therefore, regulating the electrolyte components and improving the stability of the SEI film are crucial to improving the electrochemical performance of silicon-containing lithium-ion batteries. Summary of the invention
[0003] The present invention aims to solve one of the technical problems in the related art to at least some extent. To this end, the present invention provides a battery having good interface flatness and good fast charge cycle performance.
[0004] To this end, the present invention provides a battery, comprising an electrolyte and a negative electrode plate, wherein the electrolyte comprises a first additive and a second additive, wherein the first additive has a structure shown in Formula 1; the second additive comprises at least one of tripropargyl phosphate, propyl bis(2-propynyl) phosphate, and ethyl bis(2-propynyl) phosphate; the negative electrode plate comprises a negative electrode active material, wherein the negative electrode active material comprises silicon;
[0005]
[0006] In view of the fact that the electrode interface of existing secondary batteries is easily damaged during the cycle process, the present invention provides a battery including a first additive and a second additive. The two additives are electropolymerized during battery operation and adhere to the positive and negative electrode surfaces together to maintain the flatness of their interfaces, thereby promoting the stability of the battery cycle.
[0007] Specifically, the first additive (compound of Formula 1) removes the ester group to generate a long-chain hydrocarbon polymer and a by-product Li 2 SO 4 and Li 2 CO 3 ; Among them Li 2 SO 4 It has the ability to oxidize other unsaturated groups (such as carbon-carbon triple bonds C≡C), that is, to promote the polymerization reaction of other additives. 2 CO 3 It can effectively reduce the reduction and decomposition of ethylene carbonate EC in the electrolyte at 0.75V and inhibit the formation of alkyl lithium carbonate at 0.6V, maintain the stability of the electrolyte, and reduce Li +loss and improve the cycle stability of lithium-ion batteries.
[0008] Specifically, the second additive structure contains unsaturated alkynes at both ends. When polymerization occurs, the unsaturated alkynes at both ends are used as polymerization points to form long-chain polymers. During the actual charge and discharge process, the second additive can be tightly anchored on the positive and negative electrode surfaces through C≡C without decomposing, which can maintain the flatness of the interface, improve the volume expansion and breakage problems of the silicon negative electrode, and thus promote the stability of the battery cycle. However, when the concentration of the second additive reaches a certain level, its adsorption mode will change from horizontal adsorption to vertical adsorption, hindering the migration of lithium ions, reducing the uniformity of the interface film, and resulting in increased impedance.
[0009] The first additive undergoes polymerization to generate Li 2 SO 4 It will oxidize the C≡C in the structure of the second additive and promote its bond breaking polymerization. At the same time, the reaction product is adsorbed on the interface, reducing the probability of vertical adsorption of the second additive, thereby improving the adverse effect of the second additive on the negative electrode structure, maintaining the flatness of the interface, improving the volume expansion and breakage problems of the silicon negative electrode, and achieving the effect of improving the fast charging cycle stability of the battery.
[0010] According to an embodiment of the present invention, the mass ratio of the first additive to the second additive is 1:(0.1-2), preferably 1:(0.1-1). Thus, the flatness of the battery interface can be improved, thereby improving the fast charge cycle performance of the battery.
[0011] According to an embodiment of the present invention, the battery further includes a third additive, and the third additive has a structure shown in Formula 2;
[0012]
[0013] Among them, R 12 , R 13 , R 14 Each independently selected from H, C 1 -C 6 Alkyl, C 2 -C 4 alkenyl, and R 12 , R 13 , R 14 H, R 12 , R 13 , R 14 At least one of them contains a carbon-carbon double bond;
[0014] or, R 12 and R 12 The atoms together form C 2 -C 4 Alkenyl, R 13 , R14 Each independently selected from H, C 1 -C 6 Alkyl, C 2 -C 4 alkenyl;
[0015] or, R 12 and R 13 Together with the atoms to which they are attached, they form C 3 -C 8 Cycloalkenyl, R 14 For H.
[0016] Specifically, R 12 , R 13 , R 14 At least one of them contains a carbon-carbon double bond, which can be electropolymerized during battery operation and attached to the surface of the negative electrode to maintain the flat interface of the negative electrode, thereby promoting the stability of the battery cycle. There are two main polymerization pathways: one is the olefin group breaking and repolymerization, and the cyclic ester is distributed at both ends of the polymer chain; the other is a polymerization method with a low degree of polymerization, in which the CO bond is preferentially broken, and then C=C is polymerized side by side to obtain a long-chain polymer with a large molecular weight. The polymerization process of the second pathway is more stable than that of the first pathway. However, excessive addition of the third additive will produce a large amount of long-chain polymers, which will hinder the transmission of lithium ions and significantly increase the interfacial charge transfer impedance. The first additive in this application can improve the adverse effects of the third additive on lithium ion transmission, and ultimately ensure the stable long-cycle and high-temperature storage performance of the battery. That is, the third additive is compounded with the first additive and the second additive to further maintain the flatness of the battery interface and achieve the effect of improving the stability of the battery fast charge cycle.
[0017] According to an embodiment of the present invention, R 12 , R 13 , R 14 Each independently selected from H, C 1 -C 4 Alkyl, C 2 -C 4 alkenyl, and R 12 , R 13 , R 14 H, R 12 , R 13 , R 14 At least one of them contains a carbon-carbon double bond;
[0018] or, R 12 and R 12 The atoms together form C 2 -C 4 Alkenyl, R 13 , R 14 Each independently selected from C1 -C 4 Alkyl, C 2 -C 4 alkenyl;
[0019] or, R 12 and R 13 Together with the atoms to which they are attached, they form C 7 -C 8 Cycloalkenyl, R 14 is H. Thus, the flatness of the battery interface can be improved, thereby improving the fast charging cycle performance of the battery.
[0020] According to an embodiment of the present invention, R 12 , R 13 , R 14 Each independently selected from H, C 1 Alkyl, C 2 alkenyl, and R 12 , R 13 , R 14 H, R 12 , R 13 , R 14 At least one of them contains a carbon-carbon double bond;
[0021] or, R 12 and R 12 The atoms together form C 2 Alkenyl, R 13 , R 14 Each independently selected from C 1 Alkyl, C 2 alkenyl;
[0022] or, R 12 and R 13 Together with the atoms to which they are attached, they form C 7 Cycloalkenyl, R 14 is H. Thus, the flatness of the battery interface can be improved, thereby improving the fast charging cycle performance of the battery.
[0023] According to an embodiment of the present invention, the third additive includes at least one of the following compounds:
[0024]
[0025] In this way, the flatness of the battery interface can be improved, thereby improving the fast charging cycle performance of the battery.
[0026] According to an embodiment of the present invention, the mass ratio of the first additive, the second additive, and the third additive is 1:(0.1-2):(0.1-1), preferably 1:(0.1-1):(0.1-0.2). Thus, the flatness of the battery interface can be improved, thereby improving the fast charge cycle performance of the battery.
[0027] According to an embodiment of the present invention, the battery includes an electrolyte, and based on the total mass of the electrolyte, the mass proportion of the first additive is 0.05-5%, preferably 0.1-1%. Thus, the flatness of the battery interface can be improved, thereby improving the fast charge cycle performance of the battery.
[0028] According to an embodiment of the present invention, based on the total mass of the electrolyte, the mass proportion of the second additive is 0.05-1%, preferably 0.1-0.4%. Thus, the flatness of the battery interface can be improved, thereby improving the fast charge cycle performance of the battery.
[0029] According to an embodiment of the present invention, based on the total mass of the electrolyte, the mass proportion of the third additive is 0.01-0.5%, preferably 0.05-0.1%, based on the total mass of the electrolyte. Thus, the flatness of the battery interface can be improved, thereby improving the fast charge cycle performance of the battery.
[0030] According to an embodiment of the present invention, the electrolyte further comprises a lithium salt, and the lithium salt comprises at least one of lithium hexafluorophosphate and lithium bis(fluorosulfonyl)imide, thereby reducing gas production of the battery and improving the cycle performance of the battery.
[0031] According to an embodiment of the present invention, the lithium salt includes lithium hexafluorophosphate and lithium bis(fluorosulfonyl)imide, and the mass ratio of the lithium hexafluorophosphate to lithium bis(fluorosulfonyl)imide is (2-5): 1. This can reduce the gas production of the battery and improve the cycle performance of the battery.
[0032] According to an embodiment of the present invention, the battery further comprises a positive electrode active material, wherein the positive electrode active material comprises lithium iron phosphate material, LiCoO 2 Materials, lithium-rich manganese-based materials (aLi 2 MnO 3 (1-a) LiMO 2 )、LiNi x Co y Mn z O 2 Materials, Lithium Nickel Manganese Oxide (LiNi 0.5 Mn 1.5 O 4 ) materials, lithium iron manganese phosphate materials (LiFe b Mn 1-b PO 4), wherein 0≤a≤1, 0≤b≤1, x+y+z=1, and M includes at least one of Ni, Co, and Mn. Thus, the cycle performance of the battery can be improved.
[0033] According to an embodiment of the present invention, the battery is a cylindrical battery.
[0034] According to an embodiment of the present invention, the cylindrical battery is a 18650 cylindrical battery with an energy density of 230-250Wh / kg;
[0035] The positive electrode active material of the cylindrical battery is LiNi x M 1-x O 2 , wherein M includes at least one of Co and Mn, 0.8≤x≤0.9;
[0036] The negative electrode plate comprises a negative electrode current collector and a negative electrode active material layer arranged on at least one side surface of the negative electrode current collector, and the mass proportion of silicon element in the negative electrode active material layer is 5%-8%.
[0037] Additional aspects and advantages of the present invention will be given in part in the following description and in part will be obvious from the following description, or will be learned through practice of the present invention. BRIEF DESCRIPTION OF THE DRAWINGS
[0038] The above and / or additional aspects and advantages of the present invention will become apparent and easily understood from the description of the embodiments in conjunction with the following drawings, in which:
[0039] Figure 1 SEM images showing different degrees of flatness of the negative electrode interface of the present invention. DETAILED DESCRIPTION
[0040] The embodiments of the present invention are described in detail below. The embodiments described below are exemplary and are only used to explain the present invention, and should not be understood as limiting the present invention.
[0041] It should be noted that the terms "first" and "second" are used for descriptive purposes only and should not be understood as indicating or implying relative importance or implicitly indicating the number of the indicated technical features. Therefore, the features defined as "first" and "second" may explicitly or implicitly include one or more of the features. Further, in the description of the present invention, unless otherwise specified, the meaning of "plurality" is two or more.
[0042] The endpoints and any values of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.
[0043] In order to make the present invention more easily understood, certain technical and scientific terms are specifically defined below. Unless otherwise clearly defined elsewhere in this document, all other technical and scientific terms used herein have the meanings commonly understood by those skilled in the art to which the present invention belongs.
[0044] In this document, the terms “include” or “comprising” are open expressions, that is, including the contents specified in the present invention but not excluding other contents.
[0045] As used herein, the terms "optionally", "optional" or "optionally" generally mean that the subsequently described event or circumstance may but need not occur, and that the description includes instances where the event or circumstance occurs and instances where it does not.
[0046] The amount of electrolyte additives used only accounts for a small part of the electrolyte in lithium-ion batteries, but an appropriate amount of additives can form SEI on the surface of the negative electrode active material, which is called an interfacial film in this application, and can reduce the problem of side reactions occurring after the negative electrode material directly contacts the electrolyte.
[0047] However, silicon-based negative electrodes have problems such as poor conductivity, easy crushing of particles, unstable growth of SEI, and volume expansion. These problems ultimately lead to reduced coulombic efficiency and cycle life of silicon-based lithium-ion batteries, and poor fast-charge cycle capabilities. Therefore, regulating the electrolyte composition and improving the stability of the SEI film are crucial to improving the electrochemical performance of silicon-containing lithium-ion batteries.
[0048] In view of this, the present invention provides a battery, comprising an electrolyte and a negative electrode plate, wherein the electrolyte comprises a first additive and a second additive, wherein the first additive has a structure shown in Formula 1; the second additive comprises at least one of tripropargyl phosphate (CAS: 1779-34-6), (2-propynyl) dibutyl phosphate (CAS: 18687-46-2), and ethyl diprop-2-ynyl phosphate (CAS: 69695-73-4); the negative electrode plate comprises a negative electrode active material, wherein the negative electrode active material comprises silicon;
[0049]
[0050] The battery provided by the present invention includes an electrolyte and a negative electrode containing silicon element. The electrolyte includes a first additive and a second additive, which can undergo electropolymerization during battery operation and adhere to the surface of the negative electrode, maintain the flatness of the interface of the negative electrode, improve the volume expansion and breakage problems of the silicon negative electrode, and thus promote the stability of the battery cycle.
[0051] Specifically, the second additive contains unsaturated alkynes at both ends of the structure. When polymerization occurs, long-chain polymers are formed with the unsaturated alkynes at both ends as polymerization points. During the actual charge and discharge process, the C≡C at one end of the second additive is tightly anchored on the surface of the positive and negative electrodes and then polymerized. This can maintain the flatness of the interface, improve the volume expansion and breakage problems of the silicon negative electrode, and thus promote the stability of the battery cycle. However, when the concentration of the second additive reaches a certain level, its adsorption mode will change from horizontal adsorption to vertical adsorption, hindering the migration of lithium ions and reducing the uniformity of the interface film, resulting in increased impedance and easy breakage of the negative electrode surface. The byproduct Li 2 SO 4 It has the ability to oxidize other unsaturated groups (such as C=C, C≡C), thereby promoting the polymerization reaction. For example, Li 2 SO 4 It will oxidize the C≡C in the structure of the second additive, promote its bond breaking polymerization, and reduce the probability of vertical adsorption, thereby improving the adverse effect of the second additive on the negative electrode interface and ensuring the stable long-cycle and high-temperature storage performance of the battery.
[0052] According to a specific embodiment of the present invention, the mass ratio of the first additive to the second additive is 1:(0.1-2). When there is too much first additive, the lithium carbonate content inside the battery is relatively high, which will cause CO 2 When the second additive is too much, the probability of its direct vertical adsorption at the interface is greatly increased, thereby affecting the desolvation and migration of lithium ions and being detrimental to the stability of the negative electrode surface structure. It can be selected according to actual needs. As some specific examples, the mass ratio of the first additive to the second additive can be 1:0.1, 1:0.5, 1:1, 1:2, etc., preferably 1:(0.1-1). This can improve the flatness of the battery interface, thereby improving the fast charging cycle performance of the battery.
[0053] The electropolymerization process of the compound of formula 1 during battery operation is as follows:
[0054]
[0055] The compound of formula 1 removes the ester group to generate a long-chain hydrocarbon polymer and a by-product Li 2 SO 4 and Li 2 CO 3 Among them, Li2 SO 4 It has the ability to oxidize other unsaturated groups (such as C≡C) and can promote the polymerization reaction of other additives. 2 CO 3 It can effectively weaken the reduction decomposition of ethylene carbonate in the electrolyte at 0.75V and inhibit the formation of alkyl lithium carbonate at 0.6V, maintain the stability of the electrolyte, reduce the loss of lithium ions, and improve the cycle stability of lithium-ion batteries.
[0056] Specifically, the second additive includes at least one of tripropargyl phosphate, (2-propynyl) dibutyl phosphate, and ethyl diprop-2-ynyl phosphate.
[0057] According to a specific embodiment of the present invention, the second additive includes tripropargyl phosphate (TPP). TPP is oxidized (loses electrons) before the main solvent, and the acidic corrosive substance F in the electrolyte has a strong electronegativity, which attacks the carbon core of TPP, causing the π bond in C≡C to break, thereby forming a CF covalent bond, and a chain addition reaction is carried out on the positive electrode. When TPP obtains electrons, the H protons in the electrolyte, due to their strong electrophilicity, will approach the alkynyl electron cloud of the p orbital, forming a CH covalent bond, and a chain addition reaction occurs on the negative electrode.
[0058] According to a specific embodiment of the present invention, the battery further includes a third additive, and the third additive has a structure shown in Formula 2;
[0059]
[0060] Among them, R 12 , R 13 , R 14 Each independently selected from H, C 1 -C 6 Alkyl, C 2 -C 4 alkenyl, and R 12 , R 13 , R 14 H, R 12 , R 13 , R 14 At least one of them contains a carbon-carbon double bond; or, R 12 and R 12 The atoms together form C 2 -C 4 Alkenyl, R 13 , R 14 Each independently selected from H, C 1 -C 6 Alkyl, C 2 -C 4 alkenyl; or, R12 and R 13 Together with the atoms to which they are attached, they form C 3 -C 8 Cycloalkenyl, R 14 For H.
[0061] Specifically, the polymerization reaction of the third additive can be divided into two types: (1) R 12 and R 13 At least one of them contains a carbon-carbon double bond, which can be used as a polymerization point, that is, the olefin bond is broken and then the polymerization reaction is carried out. The cyclic ester is distributed at both ends of the polymer chain. This path can be seen by FTIR spectroscopy (Fourier transform infrared spectroscopy) at 1795cm -1 (C=O) and 1063 cm -1 (CO) both show stable peaks; (2) the C=O bond in the structure of the third additive is broken, and then the carbon-carbon double bonds are polymerized side by side to obtain a large amount of long-chain polymers. Compared with the first polymerization method, the degree of polymerization of the polymer obtained by this polymerization method is lower, but the polymerization reaction is more stable. The polymer obtained after the reaction will adhere to the surface of the positive and negative electrodes, protecting the interface of the positive and negative electrodes to maintain flatness, thereby promoting the stability of the battery cycle.
[0062] According to a specific embodiment of the present invention, R 12 , R 13 , R 14 Each independently selected from H, C 1 -C 4 Alkyl, C 2 -C 4 alkenyl, and R 12 , R 13 , R 14 H, R 12 , R 13 , R 14 At least one of them contains a carbon-carbon double bond; or, R 12 and R 12 The atoms together form C 2 -C 4 Alkenyl, R 13 , R 14 Each independently selected from C 1 -C 4 Alkyl, C 2 -C 4 alkenyl; or, R 12 and R 13 Together with the atoms to which they are attached, they form C 7 -C 8 Cycloalkenyl, R 14H. This can reduce the steric effect caused by the excessive length of the carbon chain and reduce the problem of low film formation efficiency at the interface between the material and the electrolyte. At the same time, the additive can undergo polymerization in two different ways to obtain a long-chain polymer, which then adheres to the surface of the positive and negative electrodes, protecting the interface of the positive and negative electrodes to maintain flatness, thereby promoting battery cycle stability.
[0063] According to a specific embodiment of the present invention, R 12 , R 13 , R 14 Each independently selected from H, C 1 Alkyl, C 2 alkenyl, and R 12 , R 13 , R 14 H, R 12 , R 13 , R 14 At least one of them contains a carbon-carbon double bond; or, R 12 and R 12 The atoms together form C 2 Alkenyl, R 13 , R 14 Each independently selected from C 1 Alkyl, C 2 alkenyl; or, R 12 and R 13 Together with the atoms to which they are attached, they form C 7 Cycloalkenyl, R 14 is H. This further reduces the steric effect caused by the excessively long carbon chain and reduces the problem of low film-forming efficiency at the interface between the material and the electrolyte. At the same time, the additive can undergo polymerization in two different ways to obtain a long-chain polymer, which then adheres to the surface of the positive and negative electrodes, protecting the interface of the positive and negative electrodes to maintain a flat surface, thereby promoting the stability of the battery cycle.
[0064] According to a specific embodiment of the present invention, the third additive includes at least one of the following compounds:
[0065]
[0066] Specifically, the CAS number of formula 3-1 is 142429-71-8, the CAS number of formula 3-2 is 96548-13-9, the CAS number of formula 3-3 is 25326-19-6, and the CAS number of formula 3-4 is 4427-96-7.
[0067] Taking compound 3-4 as an example, its electropolymerization process during battery operation is as follows:
[0068]
[0069] According to a specific embodiment of the present invention, the mass ratio of the first additive, the second additive, and the third additive is 1: (0.1-2): (0.1-1). Different additive ratios will affect the adsorption of the actual polymer product on the surface of the interface film. When the first additive is excessive, the lithium carbonate content inside the battery is relatively high, which will cause CO 2 When the second additive is too much, the probability of its direct vertical adsorption on the interface is greatly increased, thus affecting the desolvation and migration of lithium ions; when the third additive is too much, the excess molecules are difficult to aggregate and adsorb on the interface normally, and the free molecules in the electrolyte increase. The reaction mechanism may be dominated by common redox reactions, producing CO 2 , O 2 Gases such as chlorinated polyols and chlorinated polyols can be selected according to actual needs. As some specific examples, the mass ratio of the first additive, the second additive, and the third additive can be 1:0.1:1, 1:1:0.2, 1:1:1, 1:0.1:0.1, 1:2:0.1, 1:2:1, etc., preferably 1:(0.1-1):(0.1-0.2). This can improve the smoothness of the interface and enhance the fast charge cycle performance of the battery.
[0070] According to a specific embodiment of the present invention, the battery includes an electrolyte, and based on the total mass of the electrolyte, the mass proportion of the first additive is 0.05-5%, for example, 0.05%, 0.1%, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5%, etc. When the content of the first additive is within the above range, electropolymerization can be better performed during battery operation to form long-chain polymers that adhere to the surfaces of the positive and negative electrodes, maintain a smooth interface, and achieve the effect of improving the fast charging cycle stability of the battery. In some embodiments of the present invention, based on the total mass of the electrolyte, the mass proportion of the first additive is 0.1-1%.
[0071] According to a specific embodiment of the present invention, based on the total mass of the electrolyte, the mass proportion of the second additive is 0.05-1%, such as 0.05%, 0.1%, 0.5%, 1%, etc. When the content of the second additive is within the above range, it can better undergo electropolymerization during battery operation, adhere to the surface of the positive and negative electrodes, maintain a smooth interface, and achieve the effect of improving the fast charging cycle stability of the battery. At the same time, its compound use with the first additive can also improve the adverse effect of the second additive on the stability of the battery interface, and ensure the stable long cycle and high temperature storage performance of the battery. In some embodiments of the present invention, based on the total mass of the electrolyte, the mass proportion of the second additive is 0.1-0.4%.
[0072] According to a specific embodiment of the present invention, based on the total mass of the electrolyte, the mass proportion of the third additive is 0.01-0.5%, such as 0.01%, 0.05%, 0.1%, 0.5%, etc. When the content of the third additive is within the above range, electropolymerization can be better performed during the operation of the battery to form long-chain polymers, which are attached to the surfaces of the positive and negative electrodes, maintain the smoothness of the interface, and achieve the effect of improving the fast charging cycle stability of the battery. At the same time, its compound use with the first additive and the second additive can also ensure the stable long cycle and high temperature storage performance of the battery. In some embodiments of the present invention, based on the total mass of the electrolyte, the mass proportion of the third additive is 0.05-0.1%.
[0073] According to a specific embodiment of the present invention, the electrolyte further comprises a lithium salt, and the lithium salt comprises at least one of lithium hexafluorophosphate and lithium bis(fluorosulfonyl)imide. Thus, adding the electrolyte to a lithium-ion battery can reduce the gas production of the battery and improve the cycle performance of the battery.
[0074] According to a specific embodiment of the present invention, the lithium salt includes lithium hexafluorophosphate and lithium bis(fluorosulfonyl)imide, and the mass ratio of the lithium hexafluorophosphate and lithium bis(fluorosulfonyl)imide is (2-5):1. Therefore, adding the above two lithium salts to the electrolyte at the same time can further reduce the gas production of the battery and improve the cycle performance of the battery. The mass ratio of lithium hexafluorophosphate and lithium bis(fluorosulfonyl)imide can be 2:1, 3:1, 4:1, 5:1, etc. Therefore, the ratio of the two lithium salts is controlled within the above range. Adding the electrolyte to a lithium-ion battery can reduce the gas production of the battery and improve the cycle performance of the battery.
[0075] According to a specific embodiment of the present invention, the electrolyte further includes a solvent, and the solvent includes a cyclic organic solvent and / or a chain organic solvent.
[0076] Specifically, the cyclic organic solvent may include one or more cyclic carbonates such as ethylene carbonate (EC) and propylene carbonate (PC), one or more cyclic carboxylates such as γ-butyrolactone, γ-valerolactone, and ε-caprolactone, one or more cyclic ethers such as tetrahydrofuran, 3-methyltetrahydrofuran, 1,3-dioxolane, and 1,4-dioxolane, and one or more chain sulfone compounds such as dimethyl sulfone, monofluoromethyl methyl sulfone, and trifluoromethyl isopropyl sulfone.
[0077] Specifically, the chain organic solvent may include one or more linear carbonates such as dimethyl carbonate (DMC), ethyl methyl carbonate (EMC), diethyl carbonate (DEC), methyl propyl carbonate (MPC), one or more linear carboxylates such as methyl acetate, ethyl acetate, methyl propionate, ethyl propionate, and one or more chain ethers such as ethyl ether, di(2-fluoroethyl) ether, and di(2,2-difluoroethyl) ether.
[0078] According to a specific embodiment of the present invention, the electrolyte may further include other additives, and the other additives are selected from at least one of vinylene carbonate (VC), fluoroethylene carbonate (FEC), ethylene sulfate (DTD), 1,3-propane sultone (PS), vinyl sulfite (ES), and lithium difluorobis(oxalate) phosphate (LiODFP). The mass proportion of the conventional additives in the electrolyte is 0.5-5%, for example, 0.5%, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5%, etc.
[0079] It should be noted that conventional additives are types of additives commonly used in the art, and those skilled in the art can select them according to actual needs, which will not be repeated here. The characteristics and advantages described for the above-mentioned electrolyte additives are also applicable to the electrolyte, which will not be repeated here.
[0080] According to a specific embodiment of the present invention, the battery further comprises a positive electrode active material, wherein the positive electrode active material comprises lithium iron phosphate material, LiCoO 2 Materials, lithium-rich manganese-based materials (aLi 2 MnO 3 (1-a) LiMO 2 )、LiNi x Co y Mn z O 2 Materials, Lithium Nickel Manganese Oxide (LiNi 0.5 Mn 1.5 O 4 ) materials, lithium iron manganese phosphate (LiFe b Mn 1-b PO 4 ), wherein 0≤a≤1, 0≤b≤1, x+y+z=1, and M includes at least one of Ni, Co, and Mn. Thus, the cycle performance of the battery can be improved.
[0081] According to a specific embodiment of the present invention, the positive electrode active material includes LiNi x M 1-x O 2 (M is selected from at least one of Co and Mn, 0.8≤x≤0.9). This high-nickel ternary material is the preferred positive electrode material for automotive power batteries now and in the future due to its advantages such as low cost, high energy density, high reversible capacity, and environmental friendliness. In addition, the above-mentioned high-nickel ternary material combined with the electrolyte of the present invention can further improve the cycle stability of the battery under high voltage and reduce the gas production of the battery. Specifically, x can be selected from 0.8, 0.85, 0.9, etc.
[0082] Typically, a battery includes a positive electrode sheet, a negative electrode sheet, an electrolyte, and a separator. During the battery charge and discharge process, active ions are embedded and removed back and forth between the positive electrode sheet and the negative electrode sheet. The electrolyte plays the role of conducting ions between the positive electrode sheet and the negative electrode sheet. The separator is set between the positive electrode sheet and the negative electrode sheet, mainly to prevent the positive and negative electrodes from short-circuiting, while allowing ions to pass through.
[0083] The positive electrode sheet comprises a positive electrode current collector and a positive electrode active material layer arranged on at least one side surface of the positive electrode current collector, wherein the positive electrode active material layer comprises the positive electrode active material mentioned above.
[0084] In some embodiments of the present invention, the positive electrode current collector may include a metal foil or a composite positive electrode current collector. For example, the metal foil may be aluminum foil. The composite positive electrode current collector may include a polymer material base and a metal layer formed on at least one side of the surface of the polymer material base. For example, the composite negative electrode current collector may be formed by forming a metal material (aluminum, aluminum alloy, nickel, nickel alloy, etc.) on a polymer material substrate (such as polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT) and other substrates).
[0085] In some embodiments of the present invention, the positive electrode active material layer may further include a conductive agent. As an example, the conductive agent may include at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene and carbon nanofibers.
[0086] In some embodiments of the present invention, the positive electrode active material layer may further optionally include a binder. As an example, the binder may include at least one of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), vinylidene fluoride-tetrafluoroethylene-propylene terpolymer, vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer, and fluorine-containing acrylate resin.
[0087] In some embodiments of the present invention, the positive electrode sheet can be prepared in the following manner: the components for preparing the positive electrode sheet, such as the positive electrode active material, the conductive agent, and the binder are dispersed in a solvent (such as N-methylpyrrolidone) to form a positive electrode slurry; the positive electrode slurry is coated on the positive electrode collector, and after drying, cold pressing and other processes, the positive electrode sheet can be obtained.
[0088] The negative electrode sheet includes a negative electrode current collector and a negative electrode active material layer disposed on at least one side surface of the negative electrode current collector, wherein the negative electrode active material layer includes a negative electrode active material.
[0089] In some embodiments of the present invention, the negative electrode current collector may be a metal foil or a composite current collector. For example, as the metal foil, a copper foil may be used. The composite current collector may include a polymer material base and a metal layer formed on at least one surface of the polymer material substrate. The composite current collector may be formed by forming a metal material (copper, copper alloy, nickel, nickel alloy, etc.) on a polymer material substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), etc.).
[0090] In some embodiments of the present invention, the negative electrode active material may be a silicon-containing active material for batteries known in the art. As an example, it may include at least one of the following materials: elemental silicon, silicon-oxygen compounds, silicon-carbon composites, CVD silicon, and at least one carbon material such as natural graphite, artificial graphite, soft carbon, hard carbon, mesophase carbon microspheres, and nanocarbon, wherein the mass proportion of silicon in the negative electrode active material layer is 5%-8%.
[0091] In some embodiments of the present invention, the negative electrode active material layer may further include a binder. The binder may include at least one of styrene-butadiene rubber (SBR), polyacrylic acid (PAA), sodium polyacrylate (PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), sodium alginate (SA), polymethacrylic acid (PMAA) and carboxymethyl chitosan (CMCS).
[0092] In some embodiments of the present invention, the negative electrode active material layer may further include a conductive agent, which may include at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene and carbon nanofibers.
[0093] In some embodiments of the present invention, the negative electrode active material layer may further optionally include other additives, such as a thickener (eg, sodium carboxymethyl cellulose (CMC-Na)).
[0094] In some embodiments of the present invention, the negative electrode sheet can be prepared in the following manner: the components for preparing the negative electrode sheet, such as the negative electrode active material, the conductive agent, the binder and any other components are dispersed in a solvent (such as deionized water) to form a negative electrode slurry; the negative electrode slurry is coated on the negative electrode collector, and after drying, cold pressing and other processes, the negative electrode sheet can be obtained.
[0095] The present invention has no particular limitation on the type of isolation membrane, and any known porous isolation membrane with good chemical stability and mechanical stability can be selected.
[0096] In some embodiments of the present invention, the material of the isolation membrane may include at least one of glass fiber, non-woven fabric, polyolefin membrane, aromatic polyamide membrane, polytetrafluoroethylene membrane, and polyethersulfone membrane. In some embodiments of the present invention, the thickness of the isolation membrane may be 10 μm-12 μm, for example, 10 μm, 11 μm, 12 μm, etc.
[0097] In some embodiments of the present invention, the battery is a cylindrical battery, which includes the above-mentioned electrolyte, positive electrode active material and negative electrode active material.
[0098] In some embodiments of the present invention, the cylindrical battery is a 18650 cylindrical battery with an energy density of 230-250Wh / kg;
[0099] The positive electrode active material of the cylindrical battery is LiNi x M 1-x O 2 , wherein M includes at least one of Co and Mn, 0.8≤x≤0.9;
[0100] The negative electrode plate comprises a negative electrode current collector and a negative electrode active material layer arranged on at least one side surface of the negative electrode current collector, and the mass proportion of silicon element in the negative electrode active material layer is 5%-8%.
[0101] The aforementioned electrolyte has good compatibility with the positive electrode active material and the negative electrode active material, which is beneficial to improving the electrochemical performance of the battery.
[0102] The scheme of the present invention will be explained below in conjunction with the embodiments. It will be appreciated by those skilled in the art that the following embodiments are only used to illustrate the present invention and should not be considered as limiting the scope of the present invention. Where specific techniques or conditions are not indicated in the embodiments, the techniques or conditions described in the literature in this area or the product specifications are used. The reagents or instruments used are not indicated by the manufacturer and are all conventional products that can be obtained commercially.
[0103] Example 1
[0104] 1. Preparation of electrolyte: EC and DMC with a mass ratio of 3:7 were used as solvents. After mixing, lithium salt (LiPF 6 and LiFSI), an electrolyte additive, vinylene carbonate (VC) and 1,3-propane sultone (PS), and the mixture is uniformly mixed to obtain an electrolyte;
[0105] 2. Preparation of positive electrode: LiNi 0.8 Co 0.1 Mn 0.1 O 2The positive electrode active material, conductive agent SuperP (conductive carbon black), carbon nanotubes, and adhesive PVDF (polyvinylidene fluoride) are mixed evenly in a mass ratio of 94:2.5:1.5:2, and vacuum stirred until it has a certain viscosity and uniform fluidity. Then the slurry is evenly coated on the front and back of the aluminum foil, and then dried at 85°C, cold pressed, trimmed, cut, stripped, and vacuum dried at 85°C for 10 hours. After welding the pole ears, the surface density is 30mg / cm 2 The positive electrode;
[0106] 3. Preparation of negative electrode sheet: CVD silicon, graphite material, conductive agent SuperP (conductive carbon black, SP), thickener CMC (sodium carboxymethyl cellulose), adhesive SBR (styrene-butadiene rubber emulsion) are fully mixed into a uniform slurry at a mass ratio of 7.5:87:2:1.5:2. After coating on both sides of the copper foil, it is dried at 85°C, and then cold pressed, trimmed, cut, and striped. Finally, it is dried under vacuum conditions at 85°C for 12 hours. The electrode ear is welded to obtain a surface density of 12 mg / cm 2 The negative electrode;
[0107] 4. Diaphragm: A 9μm thick polyethylene porous polymer film is used as the substrate, and a 2μm adhesive coating is coated on both sides of the substrate;
[0108] 5. Battery preparation: The positive electrode sheet, separator and negative electrode sheet are wound to obtain a core, wherein the separator is between the positive electrode sheet and the negative electrode sheet to play a role of isolation, and the core is placed in a shell (made of nickel-plated stainless steel), and the negative electrode collector is welded to the shell by laser welding. After drying, the electrolyte is injected. After standing and charging the battery cell to 4.2V at 0.1C at 45°C, the formation (forming a passivation layer) and capacity separation processes are completed to complete the preparation of the battery.
[0109] The preparation methods of the lithium ion batteries of Examples 2-28 and all comparative examples are the same as those of Example 1, except that the electrolyte compositions are different, as shown in Table 1. Among them, additive 2-1 is tripropargyl phosphate, 2-2 is propyl bis(2-propynyl) phosphate, and 2-3 is ethyl bis(2-propynyl) phosphate.
[0110] The difference between Example 29 and Example 1 is that the positive electrode active material is different. The positive electrode active material of Example 29 is lithium iron phosphate (LiFePO 4 , LFP), the actual slurry mixing ratio is LFP:SP:PVDF=95:2.5:2.5, and the battery charge and discharge voltage range is 2-3.65V.
[0111] Table 1
[0112]
[0113]
[0114]
[0115]
[0116] Among them, “ / ” means not added.
[0117] The cycle performance and negative electrode interface of the lithium ion batteries obtained in the examples and comparative examples were characterized. The characterization results are shown in Table 2.
[0118] 1. Cycle test: Charge at 1.5C constant current to 4.3V at 25℃, charge at 4.3V constant voltage to cut-off current 0.05C, then discharge at 1.0C constant current, repeat the charge and discharge steps for 500 cycles, test and record the discharge capacity of the 500th cycle and the first cycle, and divide the two to get the capacity retention rate;
[0119] 2. Interface characterization: Charge at 1.5C constant current to 4.3V at 25℃, charge at 4.3V constant voltage to a cut-off current of 0.05C, and then discharge the battery at 1.0C constant current. Repeat the charge and discharge steps for 100 cycles. Test and record the discharge capacity of the 100th cycle and the 1st cycle, and divide the two to get the capacity retention rate. The battery that has been cycled for 100 weeks was disassembled, and part of the negative electrode sheet was selected for SEM testing. According to the degree of interface flatness, it was finally divided into four levels: L1, L2, L3, and L4, as follows:
[0120] L1 (excellent): The pole piece remains flat as a whole, the particle size is uniform, and there is no obvious large crack;
[0121] L2 (good): The overall flatness of the electrode is good, there is no obvious particle separation boundary, but there are obvious large cracks in some parts;
[0122] L3 (middle): the particle boundaries are clear and not tight;
[0123] L4 (poor): The surface of the electrode is obviously plated with lithium, it is severely fragmented, and large-scale film peeling and powdering occurs during disassembly.
[0124] Table 2
[0125]
[0126]
[0127] Experimental results analysis:
[0128] As can be seen from Examples 1-19, the embodiments of the present invention compound the first additive and the second additive and add them to the lithium-ion battery, the interface flatness of the battery is high, and the cycle performance of the battery is improved. At the same time, as can be seen from Examples 20-28, when the third additive is added to the electrolyte, the interface flatness of the battery and the cycle performance of the battery are further improved. As can be seen from Examples 1 and 29, under different positive electrode material systems, the first additive and the second additive are compounded, the negative electrode interface of the battery is high in flatness, and the cycle performance of the battery is improved.
[0129] Compared with the embodiment, the solutions of comparative examples 1-6 cannot improve the flatness of the battery interface and the battery cycle life. Among them, comparative example 6 is a solution without adding additives, and comparative examples 1-5 show a certain improvement in the battery cycle life compared with it, but are still worse than the embodiment.
[0130] The effects of different additive types and contents on battery performance were tested in the examples and comparative examples of the present invention, and the specific analysis is as follows:
[0131] (1) Compared with Examples 15-21, Comparative Example 1 lacks the first additive and contains only the second additive and the third additive. The second additive is more likely to be vertically adsorbed, which hinders the migration of lithium ions and reduces the uniformity of the interface film, thereby increasing the impedance. The third additive will be affected by this, and the number of sites for polymerization adsorption will be reduced, and a large amount of the third additive will be free in the electrolyte, increasing the probability of side reactions at the interface, thereby destroying the flatness of the battery interface and reducing the cycle life of the battery.
[0132] Similarly, compared with Examples 1-28, adding only the second additive in Comparative Example 4 will also destroy the flatness of the battery interface and affect the battery cycle life;
[0133] (2) Compared with Examples 20-28, Comparative Example 2 lacks the second additive and contains only the first additive and the third additive. The mechanism of HF attack on the carbon-carbon triple bond to obtain LiF and the interfacial adsorption film cannot occur, and the acidity will rise rapidly, affecting the stability of the positive and negative electrodes and reducing the cycle life of the battery.
[0134] Similarly, compared with Examples 1-20, 22-24, adding only the first additive in Comparative Example 3 will also destroy the flatness of the battery interface and affect the battery cycle life;
[0135] Similarly, compared with Examples 15-21, adding only the third additive in Comparative Example 5 will also destroy the flatness of the battery interface and reduce the cycle life of the battery;
[0136] In summary, compounding the first additive and the second additive of the present invention can achieve better battery performance improvement than not adding the first additive or not adding the second additive. In addition, when the third additive is added, the technical effect can be further improved.
[0137] In the description of this specification, the description with reference to the terms "one embodiment", "some embodiments", "example", "specific example", or "some examples" etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples, without contradiction.
[0138] Although the embodiments of the present invention have been shown and described above, it is to be understood that the above embodiments are exemplary and are not to be construed as limitations of the present invention. A person skilled in the art may change, modify, replace and vary the above embodiments within the scope of the present invention.
Claims
1. A battery, characterized in that: The invention comprises an electrolyte and a negative electrode plate, wherein the electrolyte comprises a first additive and a second additive, wherein the first additive has a structure shown in Formula 1; the second additive comprises at least one of tripropargyl phosphate, propyl bis(2-propynyl) phosphate, and ethyl bis(2-propynyl) phosphate; and the negative electrode plate comprises a negative electrode active material, wherein the negative electrode active material comprises silicon.
2. The battery according to claim 1, characterized in that The mass ratio of the first additive to the second additive is 1:(0.1-2), preferably 1:(0.1-1).
3. The battery according to claim 1, characterized in that Also included is a third additive, wherein the third additive has a structure shown in Formula 2; Among them, R 12 , R 13 , R 14 are each independently selected from H, C1-C6 alkyl, C2-C4 alkenyl, and R 12 , R 13 , R 14 H, R 12 , R 13 , R 14 At least one of them contains a carbon-carbon double bond; or, R 12 and R 12 The connected atoms together form a C2-C4 alkenyl group, R 13 , R 14 Each is independently selected from H, C1-C6 alkyl, C2-C4 alkenyl; or, R 12 and R 13 Together with the atoms to which they are attached, they form a C3-C8 cycloalkenyl group, R 14 For H.
4. The battery according to claim 3, characterized in that R 12 , R 13 , R 14 are each independently selected from H, C1-C4 alkyl, C2-C4 alkenyl, and R 12 , R 13 , R 14 H, R 12 , R 13 , R 14 At least one of them contains a carbon-carbon double bond; or, R 12 and R 12 The connected atoms together form a C2-C4 alkenyl group, R 13 , R 14 Each is independently selected from C1-C4 alkyl, C2-C4 alkenyl; or, R 12 and R 13 Together with the atoms to which they are attached, they form a C7-C8 cycloalkenyl group, R 14 For H.
5. The battery according to claim 3, characterized in that R 12 , R 13 , R 14 are each independently selected from H, C1 alkyl, C2 alkenyl, and R 12 , R 13 , R 14 H, R 12 , R 13 , R 14 At least one of them contains a carbon-carbon double bond; or, R 12 and R 12 The connected atoms together form a C2 alkenyl group, R 13 , R 14 Each is independently selected from C1 alkyl, C2 alkenyl; or, R 12 and R 13 Together with the atoms to which they are attached, they form a C7 cycloalkenyl group, R 14 For H.
6. The battery according to claim 3, characterized in that The third additive includes at least one of the following compounds:
7. The battery according to any one of claims 3 to 6, characterized in that: The mass ratio of the first additive, the second additive and the third additive is 1:(0.1-2):(0.1-1), preferably 1:(0.1-1):(0.1-0.2).
8. The battery according to any one of claims 1 to 7, characterized in that: The battery comprises an electrolyte. Based on the total mass of the electrolyte, the mass proportion of the first additive is 0.05-5%, preferably 0.1-1%.
9. The battery according to claim 8, characterized in that Based on the total mass of the electrolyte, the mass proportion of the second additive is 0.05-1%, preferably 0.1-0.4%.
10. The battery according to claim 8, characterized in that Based on the total mass of the electrolyte, the mass proportion of the third additive is 0.01-0.5%, preferably 0.05-0.1%.
11. The battery according to claim 8, characterized in that The electrolyte further includes a lithium salt, and the lithium salt includes at least one of lithium hexafluorophosphate and lithium bis(fluorosulfonyl)imide.
12. The battery according to claim 11, characterized in that The lithium salt includes lithium hexafluorophosphate and lithium bis(fluorosulfonyl)imide, and the mass ratio of the lithium hexafluorophosphate to the lithium bis(fluorosulfonyl)imide is (2-5):
1.
13. The battery according to any one of claims 1 to 12, characterized in that: The battery also includes a positive electrode active material, which includes a lithium iron phosphate material, a LiCoO2 material, aLi2MnO3·(1-a)LiMO2 material, a LiNi x Co y Mn z O2 materials, LiNi 0.5 Mn 1.5 O4 material, LiFe b Mn 1-b At least one of PO4 materials; Among them, 0≤a≤1, 0≤b≤1, x+y+z=1, and M includes at least one of Ni, Co, and Mn.
14. The battery according to any one of claims 1 to 13, characterized in that: The battery is a cylindrical battery.
15. The battery according to claim 14, characterized in that The cylindrical battery is a 18650 cylindrical battery with an energy density of 230-250Wh / kg; The positive electrode active material of the cylindrical battery is LiNi x M 1-x O2, wherein M includes at least one of Co and Mn, 0.8≤x≤0.9; The negative electrode plate comprises a negative electrode current collector and a negative electrode active material layer arranged on at least one side surface of the negative electrode current collector, and the mass proportion of silicon element in the negative electrode active material layer is 5%-8%.
Citation Information
Patent Citations
Non-aqueous electrolyte and lithium ion battery
CN115207462A
Lithium ion battery
CN116072964A
Cited By
battery
EP4807841A1
Battery
WO2026157053A1